2020
DOI: 10.1519/jsc.0000000000003733
|View full text |Cite
|
Sign up to set email alerts
|

Can Foot Anthropometry Predict Vertical Jump Performance?

Abstract: Hawley, VS, Gurchiek, RD, and van Werkhoven, H. Can foot anthropometry predict vertical jump performance? J Strength Cond Res 36(7): 1860-1865, 2022-Vertical jumping is an important element of many sporting activities, and whether anthropometric adaptations can predict jumping performance is of interest. Few studies have specifically considered anthropometric measures of the foot and its link to performance. Furthermore, previous studies have mainly focused on a male subject pool, and whether relationships are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Therefore, it was supposed that the participants in this study were well accustomed to jumping as high as possible and would be able to use effective stretch shortening function. For anthropometric factors, a significant correlation exists between jump height and toe length in young male adults [29], between jump height and foot and toe length in young female adults [30]. For adolescent boys and girls examined here, we have no data on foot and/or toe length.…”
Section: Discussionmentioning
confidence: 86%
“…Therefore, it was supposed that the participants in this study were well accustomed to jumping as high as possible and would be able to use effective stretch shortening function. For anthropometric factors, a significant correlation exists between jump height and toe length in young male adults [29], between jump height and foot and toe length in young female adults [30]. For adolescent boys and girls examined here, we have no data on foot and/or toe length.…”
Section: Discussionmentioning
confidence: 86%
“…The results of the current investigation do not provide a clear explanation for prolonged GCTs in NCAA male athletes. Previous research has indicated that height and limb length may disproportionally affect jumping performance across different levels of athletic participation and between sexes [ 72 , 73 , 74 , 75 , 76 , 77 ]. Specifically, height and lower-extremity limb lengths in competitive male athletes have been found to associate positively with JH [ 73 , 74 , 76 ], yet these associations do not seem to hold for recreational males and females with varying levels of athletic participation [ 72 , 75 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has indicated that height and limb length may disproportionally affect jumping performance across different levels of athletic participation and between sexes [ 72 , 73 , 74 , 75 , 76 , 77 ]. Specifically, height and lower-extremity limb lengths in competitive male athletes have been found to associate positively with JH [ 73 , 74 , 76 ], yet these associations do not seem to hold for recreational males and females with varying levels of athletic participation [ 72 , 75 , 77 ]. In taller male athletes, height and lower-limb length may increase CoM displacement during the concentric phase of jumping, which in turn could provide additional time to accumulate the mechanical impulse that is ultimately responsible for determining JH [ 72 , 73 , 78 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in relative to EG, FG was likely to win higher scores during the contest, due to superior performance on slam dunk-specific MVJ. However, except the slam dunk performance, condition after warm-up (sitting vs keepingactively) [41], and foot anthropometry (length of feet and toes) [42] could also probably explain the difference between groups in MVJ. To sum up, TQCS, SVJ and MVJ seem to be key indicators in physical fitness for slam dunk performance.…”
Section: Plos Onementioning
confidence: 99%